The Meeting and Virtual Technology - Cataldo-Gonzalez, H (UNIV PEDAGOGICA & TECNOLOGICA COLOMBIA, 2023)
The article unfolds the concept of encounter from a reading of 48 of Galileo Galilei s The Assayer, developing an analysis that projects a critical interpretation of current virtual reality technology. Likewise, from a specific analysis about language, which both Friedrich Nietzsche and Hannah Arendt develop in certain writings, I argue, applying the analysis of the concept of encounter, that Galilean scientific reason suppresses, closes and rejects human perception installing in its place the modern scientific invention, namely the modern-contemporary mathematized reality, and whose current expression is digital technology. In this way, I conclude the article with a critique of the technological devices for data extraction, taking as a guideline the analytical deployment of encounter.